SUITABILITY OF DEVELOPMENT OF THE NATIONAL MARKET OF CREDIT DERIVATIVES - Koshevtsova , M. A.; Rodina , O. G. (The actual problems of regional economy development, 2020)
The article is devoted to studying of the essence of the credit derivatives market, its advantages and disadvantages, consideration of the suitability of development of the national market of credit derivatives. Categories and instruments of the derivatives market are defined. Due to the youth of the credit derivatives market, its share in the total volume of derivative transactions is still small, but has great prospects. Their scope is not limited to banking or a single market. The allocation of risk to a separate object of trade has led to the emergence of new forms of credit derivatives, where they can be an alternative to traditional insurance instruments, as well as have very individual approach to managing established risk. In the case of lending, they are simply irreplaceable, as they are a way of insuring for adverse credit risk. The functions of credit derivatives at the present stage are considered. Strategic directions of development of the domestic derivatives market are determined. It has been found that credit derivatives create the conditions for the accumulation of systemic risks, so increase the degree of probability of the adverse systemic successor caused by exogenous or endogenous reason that lead to financial market instability. These factors must be taken into account press for introduce the use of credit derivatives in the Ukrainian banking sector. The world experience of organization of credit derivatives market regulation system as a way to minimize negative consequences is analyzed. Given the world experience, we can say that the state pays much attention to the development of the financial market segment, as a market of credit derivatives, which is lacking in the Ukrainian banking sector. Using the world experience, advantages and possible negative consequences of the credit derivatives market, the credit derivatives market is necessary for the development of lending in Ukraine.